What Drives Performance in High-Risk Manufacturing? The Roles of Motivation and Discipline - Najib, Aenun; Sary, Fetty Poerwita (Journal of Business, Social and Technology, 2026)
Background: Work motivation and work discipline are widely recognized as determinants of employee performance; however, most empirical studies focus on general organizational contexts, with limited evidence from high-risk, safety-critical manufacturing environments. This gap is significant in flat glass production, where declining performance—reflected in rising absenteeism, tardiness, and disciplinary violations—may directly threaten operational reliability and safety compliance. Objective: This study examines the partial and simultaneous effects of work motivation and work discipline on employee performance in a safety-sensitive industrial setting at PT Muliaglass Float 1 Division. Methods: An associative quantitative approach was employed using data collected from 110 employees through a structured Likert-scale questionnaire. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to assess measurement validity, construct reliability, and structural relationships. Results: Work motivation and work discipline positively and significantly affect employee performance, explaining 70% of the variance (R² = 0.700). Work discipline demonstrates a stronger effect, highlighting the critical role of procedural compliance and behavioral consistency in high-risk production environments. Conclusion: Work motivation and work discipline significantly influence employee performance in a safety-critical manufacturing environment, with discipline showing a stronger effect and jointly explaining 70% of performance variance. The findings highlight the central role of procedural compliance and safety adherence in stabilizing performance in high-risk settings. Practically, organizations should align motivational programs with strong disciplinary and safety systems. The study is limited by its cross-sectional design and single-company scope; therefore, future research should adopt longitudinal approaches and incorporate additional contextual variables to enhance generalizability.